Bio‐antifelting of wool based on mild methanolic potassium hydroxide pretreatment. Issue 1 (1st August 2012) - Wang, Ping; Yuan, Jiugang; Ren, Xuehong; Cui, Li; Wang, Qiang; Fan, Xuerong
<x xml:space="preserve">Abstract</x> Covalently bound lipids cover the wool surface and make enzymatic degradation of wool scales very difficult. In this paper, methanolic potassium hydroxide (MPH) pretreatment was used prior to enzymatic treatment of wool with protease, aiming at hydrolyzing the outmost lipids on the wool surface and promoting the subsequent proteolytic reaction. The efficacy of lipid removal from the fiber surface and the properties of the protease‐treated wool were evaluated. The results indicated that mild MPH pretreatment with 0.10 mol/L MPH for 10 min improved the wettability of the wool without adverse impacts on its mechanical properties. The wetting time and area shrinkage of the wool fabric reached 0.5 s and 5.6%, respectively, and the strength loss was within the acceptable range. Pretreatment with high concentrations of MPH for longer times led to significant damage to the wool fibers and caused heavy strength loss, without improving the antifelting properties after protease treatment. Thus, the combination of mild MPH and protease treatments endowed the wool with desirable properties in contrast to the treatment with protease alone.